2002
DOI: 10.1097/00003246-200206000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Catheter replacement in continuous arteriovenous hemodiafiltration: The balance between infectious and mechanical complications*

Abstract: When catheters were changed as clinically indicated, they remained significantly longer in situ vs. being replaced routinely every 5 days; infectious and mechanical complications were comparable. The incidence of catheter sepsis was low (2.2%), and no prosthesis infection occurred. Catheter replacement when clinically indicated seems to be as safe as routine replacement every 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…The higher mortality in this population may compete with catheterrelated bloodstream infection. In agreement with previous reports (17,19), the most frequently cultured microorganism was Staphylococcus epidermidis. Predominance of fungi may be, in part explained by greater broad-spectrum, predominantly antibacterial, antibiotic use in CRRT patients than IHD, as suggested by greater antimicrobial use noted in the Table 1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The higher mortality in this population may compete with catheterrelated bloodstream infection. In agreement with previous reports (17,19), the most frequently cultured microorganism was Staphylococcus epidermidis. Predominance of fungi may be, in part explained by greater broad-spectrum, predominantly antibacterial, antibiotic use in CRRT patients than IHD, as suggested by greater antimicrobial use noted in the Table 1.…”
Section: Discussionsupporting
confidence: 93%
“…Based on our results and the results of others (19,30), we recommend against this practice for critical patients admitted in intensive care units who still require acute vascular access for IHD. However, the CRRT group demonstrated an increased risk after 10 days.…”
Section: Discussionmentioning
confidence: 71%
“…The catheterization duration (7 days) reported in this study was similar to those reported in previous studies (5,8,(15)(16)(17)(18), ranging from 4.2 days (16) to 12.0 days (5). This short-term indwelling duration suggests that the extraluminal route of cathetertip colonization predominated (19).…”
Section: Discussionsupporting
confidence: 88%
“…As for ICU patients, the incidence rates of catheter colonization and catheter-related bloodstream infection have been reported to be 8-31/1,000 catheter days [12] and 1.5-19/1,000 catheter days [13][14][15][16], respectively. Actually, however, reports on hemodialysis catheter-related infections in ICU patients are still limited [16,17]. One such report identified no significant difference in the incidence rates of catheter colonization and catheter-related bloodstream infection between hemodialysis and central venous catheters [16].…”
Section: Discussionmentioning
confidence: 99%